Young-Onset GI Cancer - Aharon, Irit Ben; Barreto, Savio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the last decade, the incidence of cancer in young patients has increased in several cancer types according to the US Surveillance, Epidemiology and End Result (SEER) data and other worldwide registries. Recently, Sung and colleagues published an extensive pooled analysis from the US in Lancet Public Health, which revealed a dramatic increase in cancer incidence among younger adults (aged 25-49 years), mainly in "obesity-related" cancers, most of which occur in the gastrointestinal (GI) tract. Several studies over the past decade have indicated a significant increase in colorectal cancer incidence among young adults below the age of 50 years. Current evidence suggests that the majority of early-onset GI cancers are sporadic and harbor no familial etiology, indicating the potentially significant role of environmental and behavioral factors in their pathogenesis. Furthermore, the gut microbiome has been proposed to play a key role in CRC carcinogenesis. The scope of this Special Issue of Cancers is to highlight perspectives regarding biology, etiology, late-term toxicities and quality of life which are unique and relevant to young-onset GI cancer cases.